Issue about finishing the floor works on 4th & 5th floor - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the issue about finishing the floor works on 4th & 5th floor of BRACU new campus building.